2012
DOI: 10.5251/abjna.2012.3.4.175.191
|View full text |Cite
|
Sign up to set email alerts
|

Fruit thinning with specific reference to citrus species : A review

Abstract: Fruit thinning is defined as the removal of certain flowers or clusters of flowers or individual fruitlets after fruit set and natural dropping have occurred.it improves fruit yield and quality and return bloom for the following year.There are three types of thinning namely:hand,mechanical and chemical.Chemical thinning is the most common type of thinning.Various chemicals are used for thinning.Still many more are being introduced into the market and they have varying effects on fruit quality and yield,dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 14 publications
0
23
0
2
Order By: Relevance
“…Ouma (2012) pointed out that thinning improves quality, as it provides better fruit size, shape, color and higher SS content. Fruit size can be improved by increasing carbohydrate availability from the source or by increasing sink capacity.…”
Section: Fruit Thinning and Hormone Applicationmentioning
confidence: 99%
“…Ouma (2012) pointed out that thinning improves quality, as it provides better fruit size, shape, color and higher SS content. Fruit size can be improved by increasing carbohydrate availability from the source or by increasing sink capacity.…”
Section: Fruit Thinning and Hormone Applicationmentioning
confidence: 99%
“…Different studies confirmed the effect of chemical thinning agents (synthetic auxins) on mandarin thinning [4,5]. However, many chemicals are being released by the chemical companies [1] and other thinning methods could be assessed.…”
Section: Introductionmentioning
confidence: 95%
“…Fruit thinning is the removal of certain flowers or fruitlets in order to improve fruit yield and quality and return bloom for the following year [1]. The final size of citrus fruits depends on the degree of competition among them, apart from other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Secara umum, buah pada tanaman dengan kelebatan yang tinggi akan mempunyai ukuran buah yang lebih rendah dibandingkan tanaman yang berbuah jarang (Ouma 2012). Pada penelitian penjarangan buah apel, disimpulkan bahwa tanaman yang mempunyai jumlah buah yang lebih rendah karena dijarangkan akan mempunyai buah dengan ukuran berat dan TPT yang lebih tinggi dibandingkan kontrol (Meland 2009).…”
Section: Sifat Fisik Buahunclassified